Vehicle influence on calcium hydroxide pastes diffusion in human and bovine teeth - Ribeiro Camargo, Carlos Henrique; Bernardineli, Norberti; Valera, Marcia Carneiro; Talge de Carvalho, Claudio Antonio; de Oliveira, Luciane Dias; Menezes, Marcia Maciel; Afonso, Samira Esteves; Gasparoto Mancini, Maria Nadir (Blackwell Publishing, 2006)
The purpose of this study was to compare the pH and calcium ion liberation after use of calcium hydroxide pastes with different paste vehicles in human or bovine teeth. Ninety-two single-rooted human and bovine roots were used. The roots were instrumented and an external cavity preparation was performed. The roots were divided in to human and bovine groups. Each group was subdivided into four subgroups (SB) according to the vehicle:SB1, detergent; SB2, saline; SB3, polyethylenoglycol + camphorated paramonochlorophenol (Calen PMCC) and SB4, polyethylenoglycol + furacyn paramonochlorophenol (FPMC). Specimens were immersed into saline solution at 37 degrees C and after 7 and 14 days pH and calcium ion measurements were made. The results were analyzed by ANOVA and Tukey tests (P < 0.05). There was no statistical difference between bovine and human teeth in the pH analysis (P < 0.05), but bovine teeth provided larger calcium ion liberation than human teeth. Calen PMCC was statistically more effective for pH increase and calcium ion liberation in all analyses, followed by FPMC and saline. Detergent showed the lowest pH alterations and calcium ion liberation. The period of 14 days showed more calcium ionic liberation than the 7-day period.
Keywords: calcium hydroxide; dentin permeability; intracanal dressing